Livestock production in central Mali: Environmental factors affecting weight in traditionally managed goats and sheep - Wilson, R.T. (Cambridge University Press, 1987)
A study undertaken to examine the factors affecting weight in traditionally managed goats and sheep in an agro-pastoral system in Niono from 1978 to 1984. Considers birth weight & weights to weaning, weights from weaning to maturity, and breeding female post-partum weights. Discusses effects of climate on specific age and sex groups.